Evaluasi Pemberian Infusa Daun Kelor (Moringa Oleifera) Terhadap Performa, Kualitas Telur dan Status Kesehatan Ayam Petelur Strain Lohmann Brown: Evaluation of Kelor (Moringa oleifera) Leave Infusion on the Performance, Egg Quality, and Health Status of Lohmann Brown Laying Hens - septiawan, andri; Sumiati; Mutia, Rita (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2024)
This study aims to evaluate the effect of Kelor (Moringa oleifera) leaf infusion on the performance, physical quality of eggs, and health status of Lohmann Brown laying hens. This study used 120 laying hens aged 84 weeks. This study used a Completely Randomized Design (CRD) with 3 treatments (P0: Drinking water without infusion, P1: drinking water containing 5% infusion (5 cc 100cc-1), P2: drinking water containing 10% infusion (10 cc 100cc-1) and 5 replications with 8 chickens in each replication. The data obtained were tested using analysis of variance (ANOVA), and any significant difference was continued with the Tukey test. The feed used was commercial laying hen feed produced by PT. Kerta Mulya Saripakan. The results showed that the administration of moringa leaf infusion in drinking water at a level of 5% (5 cc 100cc-1) significantly increased (p<0.05) hen day egg production (HDP), egg mass production, haugh units (HU), and egg yolk color scores, while it reduced the feed conversion ratio (FCR) value. A level of 5% was able to maintain the health of laying hens. It can be concluded that the administration of Kelor leaf infusion in drinking water maintains the production of laying hens.